Предмет: Алгебра,
автор: Аноним
Решите срочно !!!!!!!
3(х - 2 ) - 7 ( 2 - х ) =
и
2 х - 3 х + 7 ( х - 9 ) - 7 =
Ответы
Автор ответа:
0
3(x-2)-7(2-х)=3х-6-14+7х=10х-20.
2х-3х+7(х-9)-7=2х-3х+7х-63-7=6х-70.
2х-3х+7(х-9)-7=2х-3х+7х-63-7=6х-70.
Автор ответа:
0
а там только 7х
Автор ответа:
0
вы как считали вообще?
Автор ответа:
0
мой ответ верен
Похожие вопросы
Предмет: Информатика,
автор: ayanatg2811
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: dmutrenko8877
Предмет: Математика,
автор: Музон1
Предмет: Химия,
автор: drakosha1402